Integrated Management Systems and the profitability of Contractors in contractor companies linked to the mining sector (LACCEI, 2024)
The sector of contractor companies, directly linked to mining, constitutes a motor of economic development and therefore of improvement in the quality of life of the inhabitants of the locality in which they operate. Like other business organizations, they are considered complex entities and need disruptive management models that take into account economic and social complexity and that allow sustainability by generating profitability. The purpose of the study is to determine the relationship between the integrated management system (GIS) and the profitability of a contractor company in the mining sector, Cajamarca, 2022. For this, a quantitative, correlational, non-experimental cross-sectional study has been carried out. Has been used using as an instrument that has a validity of total applicability and a reliability of 0.88. The results obtained glimpse the level of significance in each relationship, integrated management systems and profitability (p= .000 r= 812) processes and profitability (p= .000 r= 741) interest group and profitability (p= .005 r= 597). It is concluded that the Integrated Management System is directly and positively related to the profitability of the contractor company belonging to the mining sector.